Peran Tradisi Peambo bagi Kehidupan Anak di Desa Pebaoa Kecamatan Kulisusu Utara Kabupaten Buton Utara - Veni Gusniar; La Niampe; Wahyu Rustiani Komang (Jurusan Tradisi Lisan, Fakultas Ilmu Budaya, Univeritas Halu Oleo, 2023)
This study aims to find out the role, function, and meaning of the implementation of the Peambo tradition for babies in Pebaoa Village, North Kulisusu District, North Buton Regency, using a qualitative descriptive research type. The results of this study indicate that the Peambo Tradition is still trusted by the local community, in shaving babies' hair and is still adhered by the local community it’s meaning as a body and soul cleanser for newborns eight or forty days old. In the past, during the Peambo ritual, the baby's hair was shaved clean during the Peambo ritual. The role of the Peambo tradition are: (1) As a form of cleansing the child's soul, (2) Acting as a Cure for Congenital Diseases, (3) Acting as an Introduction to Culture to Children in Pebaoa Village (4) Acting as an Introduction to Islam to children in Pebao Village. The function is to serve as a bonding agent for a sense of kinship and a sense of brotherhood as well as a sense of mutual assistance among fellow communities. The meaning of the Peambo tradition for the community is as a form of gratitude to God Almighty who has blessed offspring to the organizers of Peambo, providing safety for the baby and the mother of the baby, so that the community carries out this tradition. The process consists of (1) Collecting tools, materials, and deliberations (2) Pobaca'a Dho'a, Haroa Dhulano Ana, Pompaheia Karuno Ana, Molawa Ana , Haroa Dho'a Salama (3) Closing stage.